Inheritance of seedling heat tolerance and maturity traits in diallel F1 hybrids of pearl millet (Pennisetum glaucum) - YADAV, ASHOK KUMAR; NARWAL, M S; ARYA, RAJESH KUMAR (The Indian Journal of Agricultural Sciences, 2014)
A half-diallel mating system involving ten parents was used in the present study to determine the nature of gene action and genetic parameters in pearl millet [Pennisetum glaucum (L.) R. Br.]. The Vr–Wr graph indicated over dominance for emergence rate, number of leaves/seedling, seedling height, fresh weight/seedling, dry weight/seedling, panicle emergence, number of effective tillers/plant, plant height, ear weight/plant, dry fodder yield/plant, grain yield/plant and total biological yield/plant. Partial dominance was observed for seedling thermo-tolerance index and ear length. The epistasis was found to be absent for emergence rate, seedling thermo-tolerance index, seed to seedling thermo-tolerance index, ear length, seedling height and plant height. The additive component of variance (D) had a significant presence for STI and SSTI in both the stress environments. The effect of over dominance was also reflected by higher degree of overall dominance effect (h2) for both these characters. The h2 component was significant for germination, emergence rate, number of leaves/seedling, seedling height, fresh weight/seedling, dry weight/seedling, panicle emergence, number of effective tillers/plant, plant height, ear length, ear weight/plant, dry fodder yield/plant, grain yield/plant and total biological yield/plant in all the three environments, while, for the remaining characters and environments it was non-significant. The inter relationship of the H1 and H2 parameters is reflected in the allied genetic parameter H2/4H1 index that estimates the proportion of genes with positive/negative effects, showing dominance in the parents. The value of this index was less than the expected values of 0.25 for all the characters in all the three environments indicating the asymmetrical distribution of dominant genes having positive and negative effects in parents. The ratio h2/H2 denotes the number of gene groups exhibiting dominance. The value of this ratio indicated one group of genes for STI, SSTI, germination, and number of effective tillers/plant. The character panicle emergence indicated two gene groups exhibiting dominance. Three gene groups were shown by the characters, i.e. seedling height, fresh weight/seedling and dry weight/seedling. The characters, ear weight/plant (stress environments), dry fodder yield/plant and grain yield/plant (stress environments) exhibited four gene groups. Five gene groups were exhibited by the characters, namely, plant height, ear length and total biological yield/plant.